UPAYA MENINGKATKAN KEAKTIFAN SISWA MENGGUNAKAN MODEL KOOPERATIF TIPE TGT BERBANTUAN WORDWALL PADA MATA PELAJARAN MATEMATIKA KELAS IV SDN 101934 CITAMAN - Friska, Diva; Safrida Napitupulu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the increase in student activity in mathematics subjects through the application of the TGT (Teams Games Tournament) cooperative learning model assisted by wordwall. This study uses the Classroom Action Research (CAR) approach, this study is a quantitative study. Data collection instruments in this study were student observation sheets, questionnaires and documentation. This study involved fourth grade students of SDN 101934 Citaman as the main participants. The results showed that student activity increased significantly, by showing the average percentage value of student activity observation sheets in cycle I of 56.60% (moderate category) and in cycle II of 80.26% (good category), so it can be seen that there is an increase in the average percentage value from cycle I to cycle II. Based on the explanation above, it can be concluded that using the TGT type cooperative model assisted by wordwall can increase student activity in Mathematics subjects in grade IV SDN 101934 Citaman.